Charge Photogeneration and Recombination in Fluorine-Substituted Polymer Solar Cells - Hu, Rong; Liu, Yurong; Peng, Jun; Jiang, Jianjun; Qing, Mengyao; He, Xiaochuan; Huo, Ming-Ming; Zhang, Wei (Frontiers in Chemistry, 2022)
In this contribution, we studied the effect of fluorine substitution on photogenerated charge generation, transport and recombination in polymer solar cells. Two conjugated polymer materials, PBDTTT-E (fluorine-free) and PTB7 (one fluorine substitution) were compared thoroughly. Meanwhile, various characterization techniques, including atomic force microscopy, steady-state spectroscopy, transient absorption spectroscopy, spectroelectrochemistry and electrical measurements were employed to analyse the correlation between molecular structure and device performance. The results showed that the influence of fluorine substitution on both the exciton binding energy of polymer and the carrier recombination dynamics in ultrafast time scale on the polymer was weak. However, we found that the fluorine substitution could enhance the exciton lifetime in neat polymer film, and it also could increase the mobility of photogenerated charge. Moreover, it was found that the SOMO energy level distribution of donor in PTB7:PC71BM solar cell could facilitate hole transport from the donor/acceptor interface to the inner of donor phase, showing a better advantage than PBDTTT-E:PC71BM solar cell. Therefore, fluorine substitution played a critical role for high-efficiency polymer solar cells.